MOTORCYCLE POTENTIAL PROBLEMS IN JAKARTA - Sunggiardi, Reza; Suryo Putranto, Leksmono (Jurnal Transportasi, 2009)
After the economic crisis in 1997, motorcycles become a popular transport mode in Indonesian cities.However this condition leads to large number of violation and accident rate. This study tried to discuss howthis problem started and what possible measure can be taken to solve the problems, mainly based on literaturereview. The traffic data used were compiled from the data provided by PT Pamintori Cipta. Interview surveywas conducted to find people perception of motorcycles issues. The conclusion suggests that there is a needof further comprehensive study to find out what condition that makes motorcyclists voluntary return to usepublic transport and social engineering and intensive training program should be implemented for youngergeneration to improve traffic condition in Jakarta.Keywords : motorcycle violation, traffic safety, and public transport.